2020
DOI: 10.1007/s10940-020-09449-7
|View full text |Cite
|
Sign up to set email alerts
|

Prying Open the Black Box of Causality: A Causal Mediation Analysis Test of Procedural Justice Policing

Abstract: Objectives Review causal mediation analysis as a method for estimating and assessing direct and indirect effects. Reexamine a field experiment with an apparent implementation failure. Test procedural justice theory by examining to which extent procedural justice mediates the impact of contact with the police on police legitimacy and social identity. Methods Data from a block-randomised controlled trial of procedural justice policing (the Scottish Community Engagement Trial) were analysed. All constructs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…A normative motivation is related to the idea of a duty to obey the police even when in disagreement with their commands, while an instrumental motivation is related to a fear-based obedience. Empirical data often confirm that these are two separate constructs, albeit negatively correlated (Posch et al 2020). But in the context of São Paulo, the authors show that the two motivations could not be empirically differentiated and rather formed one bipolar scale moving from instrumental to normative.…”
Section: Police Legitimacy As a Coercive-consensual Continuummentioning
confidence: 99%
See 2 more Smart Citations
“…A normative motivation is related to the idea of a duty to obey the police even when in disagreement with their commands, while an instrumental motivation is related to a fear-based obedience. Empirical data often confirm that these are two separate constructs, albeit negatively correlated (Posch et al 2020). But in the context of São Paulo, the authors show that the two motivations could not be empirically differentiated and rather formed one bipolar scale moving from instrumental to normative.…”
Section: Police Legitimacy As a Coercive-consensual Continuummentioning
confidence: 99%
“…I test whether shifts in perceptions of overpolicing and underpolicing lead to more favorable views about personal use of violence outside the scope of the state, where the mechanism of this potential relationship involves the undermining of judgements about the legitimacy of legal authority. Previous work has identified a number of socially desirable downstream effects of police legitimacy, including greater levels of (self-reported) voluntary compliance with the law (Papachristos, Meares, and Fagan 2012;Jackson et al 2012) and willingness to proactively cooperate with the police (Murphy, Hinds, and Fleming 2008;Jackson et al 2020). Jackson et al (2013) suggested another consequence: "the belief that it is morally unacceptable to use violence to protect oneself, violence to take revenge and resolve disputes, and violence to achieve certain political objectives" (p. 481).…”
Section: Acceptability Of Private Use Of Violencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Saulnier and Sivasubramaniam (2021) established a significant mediating effect of procedural justice between interactions and distributive justice. Also, Pósch (2020) established a significant mediating role of procedural justice between police legitimacy and social identity. Finally, Lai et al (2022) establish a significant mediating effect of procedural justice between media trust, victimization and involuntary contact with police.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The former includes task-specific evaluations of police conduct (like the positive expectation that officers are, and will be in the future, effective and procedurally fair), whereas the latter consists of perceptions that the police has the right to rule and the authority to govern (Oliveira et al, 2020;Gur and Jackson, 2020). Crucially, PJT posits that the effect of police-citizen contact on police legitimacy is mediated by beliefs of trust in legal authority, and perceptions of police fairness, in particular, play a key role in transmitting that effect (Sunshine and Tyler, 2003;Pósch, 2021).…”
Section: Police Stops and Legal Attitudesmentioning
confidence: 99%